Effect of a recirculated air curtain with incomplete coverage of room width on the protection zone in ventilated room. (1st July 2022) - Liu, Yu; Qiu, Kaiying; Shao, Xiaoliang; Shi, Penglei; Liu, Yemin
Abstract: An air curtain is an aerodynamic barrier for contaminants and is frequently installed in the doorway to separate indoor and outdoor spaces. There are few studies on the isolation of areas within a room. In this study, the effect of a recirculated air curtain, which did not completely cover the width of the room, i.e., an incomplete air curtain, was investigated when used inside a ventilated room. The steady contaminant distributions were analyzed numerically. The impacts of air curtain length, air extract position in the air curtain, and position of the contaminant source were studied. The results for the incomplete air curtain were compared with those for complete air curtain and traditional ventilation dilution. The results showed that installing an additional incomplete and recirculated air curtain could reduce the pollution in the protection zone compared with traditional ventilation. The concentrations of contaminant could be reduced by 30.8 and 43.9% in the subzone covered by the air curtain and that not completely covered by the air curtain, respectively. When the curtain length exceeded the source position, the direct invasion of high pollution could be prevented. A relative concentration deviation of up to 26.1% was caused by different air extract positions. Under the coupled airflow field resulting from air supply jets, recirculated curtain airflow, and airflow surrounding exhaust air outlets, a complete air curtain was not necessarily a better choice. This study provides guidance for the flexible use of incomplete and recirculated air curtains for the maintenance of protection zones. Highlights: An incomplete and recirculated air curtain was studied when used in a ventilated room. Effects of curtain length, air extract position and source position were evaluated. Direct invasion of high pollution was prevented once air curtain exceeded the source. Different air extract positions caused a maximum concentration deviation of 26.1%. A complete air curtain did not necessarily create the lowest concentration.